Catching a wave: reclaiming feminism for the 21st century - Dicker, Rory Cooke; Piepmeier, Alison (Northeastern University Press, 2003)
Young women today have benefited from the strides made by grassroots social activists in the 1960s and 1970s, yet they are hesitant to identify themselves as feminists and seem apathetic about carrying the torch of older generations to redress persistent sexism and gender-based barriers. Contesting the notion that we are in a post-feminist age, this collection of essays identifies a third wave of feminism. The contributors argue that the next generation needs to develop a politicized, collective feminism that both builds on the strategies of second wave feminists and is grounded in the material realities and culture of the 21st century. Organized into five sections which mirror the stages of consciousness-raising, the book looks at a broad range of perspectives on the diversity, complexity, multiplicity and playfulness of the third wave. It is also a call to action for new voices to redefine a feminism that is not only personally aware, but also politically involved. (source: Nielsen Book Data)
Section: x, 338 p. ; 24 cm Table des matières Introduction / Rory Dicker and Alison Piepmeier The "big lie": false feminist death syndrome, profit, and the media / Jennifer L. Pozner In a word, Baywatch / Susannah B. Mintz. Reviving Lolita ; or, because junior high is still hell / Alyssa Harad "That's not fair!" : nurturing girls' natural feminism / Nancy Gruver Voices and visions : a mother and daughter discuss coming to feminism and being feminist / Roxanne Harde and Erin Harde Please–stop thinking about tomorrow : building a feminist movement on college campuses for today / Sarah Boonin Who's the next Gloria? : the quest for the third wave superleader / Jennifer Baumgardner and Amy Richards Buffy the vampire slayer : the next generation of television / Michele Byers Third World, third wave feminism(s) : the evolution of Arab American feminism / Susan Muaddi Darraj Feminism's family problem : feminist generations and the mother-daughter trope / Astrid Henry Do the ladies run this– ? Some thoughts on hip-hop feminism / Gwendolyn D. Pough The transfeminist manifesto / Emi Koyama Hearing the daughter voice : The Bat Kol as Rrrabbi Grrrl / Alana Suskin Rocking the gender order / Mimi Schippers Pranks and fake porn : doing feminism my way / Kristina Sheryl Wong Afterword / Katha Pollitt and Jennifer Baumgardner.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; féminisme pop; militance; premier cycle; périodes historiques; soc2014; thématiques; transféminisme; troisième vague

The trouble with nature: sex in science and popular culture - Lancaster, Roger N. (University of California Press, 2003)
Roger N. Lancaster provides the definitive rebuttal of evolutionary just-so stories about men, women, and the nature of desire in this spirited expose of the heterosexual fables that pervade popular culture, from prime-time sitcoms to scientific theories about the so-called gay gene.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme pop; genre; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; soc2014; thématiques; études culturelles

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis